Using Insurance Claims and Demographic Data for Surveillance of Children’s Oral Health - Keith E. Heller, DDS, DrPH; Stephen A. Eklund, DDS, MHSA, DrPH; Brian A. Burt, BDS, MPH, PhD, Daniel (Blackwell Publising, 2004)
This paper examines the utility of using private insurance and Medicaid dental claims as well as demographic data for assessing the oral health of children aged 5- 12 years in Genesee County, Michigan, communities.